2020
DOI: 10.3167/arms.2020.030111
|View full text |Cite
|
Sign up to set email alerts
|

Expat, Local, and Refugee

Abstract: In migration studies, humanitarian work and workers are studied as benefactors or managers of migrants and refugees. This article inverts the gaze from “researching down” refugees to “studying up” the humanitarian structure that governs them. The article studies how the humanitarian industry ballooned after the Syrian refugee response in Jordan due to the influx of expatriate humanitarians as economic migrants from the global North to refugee situations in the host country in the global South. It examines the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In line with earlier studies (Muñoz-Arce & Duboy-Luengo, 2023;Pentaraki & Dionysopoulou, 2019;Reininger et al, 2022), this research showed that precarity affects not only aid-recipients as is often thought, but also university-educated professionals such as aid workers. Prior studies on aid work discussed the uneven distribution of labour precarity and the intersection between existing (colonial) power inequalities and labour conditions (Farah, 2020;Ong & Combinido, 2018;Pascucci, 2019). This study builds upon these works but adds a layer of complexity by looking at precarity through the lens of emotions and shows the comparability of the above-mentioned emotions and experiences of precarity between national and international aid professionals.…”
Section: Precarious Subjectivitiesmentioning
confidence: 91%
See 3 more Smart Citations
“…In line with earlier studies (Muñoz-Arce & Duboy-Luengo, 2023;Pentaraki & Dionysopoulou, 2019;Reininger et al, 2022), this research showed that precarity affects not only aid-recipients as is often thought, but also university-educated professionals such as aid workers. Prior studies on aid work discussed the uneven distribution of labour precarity and the intersection between existing (colonial) power inequalities and labour conditions (Farah, 2020;Ong & Combinido, 2018;Pascucci, 2019). This study builds upon these works but adds a layer of complexity by looking at precarity through the lens of emotions and shows the comparability of the above-mentioned emotions and experiences of precarity between national and international aid professionals.…”
Section: Precarious Subjectivitiesmentioning
confidence: 91%
“…This in turn leads to short-term contracts for employees, as job security depends on funding. These neoliberal structures are accompanied by structures of ongoing coloniality which means that precarious labour conditions are differentially distributed between national and international professionals, which is discussed below (Farah, 2020;Ong & Combinido, 2018;Pascucci, 2019).…”
Section: Humanitarianism and Neoliberalism In Jordanmentioning
confidence: 99%
See 2 more Smart Citations
“…(Jerash camp, Palestinian no ID, Male,[30][31][32][33][34][35] This is also corroborated by other interviewees. Often they are asked to do the same type of work as a staff member but only receive some compensation for travel expenses (this was also reported by Farah, 2020) or no compensation at all. For example, one Syrian who worked as a volunteer for a radio station noted that whereas a Jordanian volunteer received a compensation of 100-150 JD to cover transportation, a Syrian would not receive any compensation, though it was noted that with time he received something.…”
Section: Macro-level: Political Capture Of the Policy Environmentmentioning
confidence: 99%